The Swerve and Ancient Materialism - Nail, Thomas; Kolozova, Katerina (Identities: Journal for Politics, Gender and Culture, 2022)
Author(s): Thomas Nail and Katerina Kolozova Title (English): The Swerve and Ancient Materialism Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 58-71 Page Count: 13 Citation (English): Thomas Nail and Katerina Kolozova, “The Swerve and Ancient Materialism,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 58-71. Author(s) Biography Thomas Nail, University of Denver Thomas Nail is a Distinguished Scholar and Professor of Philosophy at the University of Denver and author of numerous books, including The Figure of the Migrant, Theory of the Border, Marx in Motion, Theory of the Image, Theory of the Object, Theory of the Earth, Lucretius I, II, III, Returning to Revolution, and Being and Motion. His research focuses on the philosophy of movement. Katerina Kolozova, Institute of Social Sciences and Humanities, Skopje Dr. Katerina Kolozova is Executive Director, senior researcher and full professor at the Institute of Social Sciences and Humanities, Skopje, and a professor of political philosophy at FMK-Belgrade. She has published many influential articles in a number of international journals, as well as several books. These include: Capitalism’s Holocaust of Animals: A Non-Marxist Critique of Capital, Philosophy and Patriarchy (Bloomsbury Academic), as well as Cut of the Real: Subjectivity in Poststructuralist Philosophy (Columbia University Press).